Regulatory Reforms to Unlock Long-Term Growth in Turkey - Gönenç, Rauf (OECD Economics Department Working Papers, 2010)
In the 2000s, Turkey has enjoyed rapid catching-up. This was possible despite the adverse business environment, as the semi-formal and informal economy had a significant contribution to the expansion of the private sector. Productivity growth was strong, but labour utilisation remained very low. Looking forward, higher employment and productivity growth will not be possible without profound regulatory reforms of minimum wages, severance payments, social security contributions and flexible job contracts. These reforms have been discussed for a long time, but political obstacles prevented implementing them. Resolving this deadlock calls for advancing an integrated strategy of labour reforms and formalisation via experimenting with new regulation on the voluntary basis to identify the most successful solutions that can be later rolled out to the whole economy. Moreover, Turkey has to ease further anti-competitive product market regulations by reducing barriers to entrepreneurship and foreign direct investment, and by limiting government involvement in business. A successful implementation of these reforms would allow Turkey to enjoy golden decades. This paper relates to the 2010 OECD Economic Review of Turkey (www.oecd.org/eco/surveys/turkey)